Vulvovaginal atrophy: issues of treatment and rehabilitation: A review - Diana M. Ampilogova; Antonina G. Solopova; Dmitry V. Blinov; Evgeny E. Achkasov; Daria A. Petrenko; Daniil I. Korabelnikov (IP Berlin A.V., 2022)
The review presents data on the management tactics of women with vulvovaginal atrophy in patients of reproductive age and menopause. The influence of vulvovaginal atrophy on the psycho-emotional and sexual spheres, modern methods of diagnosis and therapy of this pathology are considered. Special attention is paid to the role of rehabilitation and an integrated interdisciplinary approach to patients with symptoms of atrophic changes in the urogenital tract: the experience of rehabilitation measures is highlighted on the example of foreign and local studies, the effectiveness of "prerehabilitation" at the stage of the period from diagnosis to treatment is indicated. There is still a need for further studies of complex rehabilitation and its implementation in clinical recommendations.